A study on effectiveness of promotional tools used by Epic Evolution (M) Sdn Bhd / Nurain Yahaya - Yahaya, Nurain (Faculty of Business and Management, 2011)
Epic Evolution (M) Sdn Bhd, it was operates on early 1990, it was a full service event management company. Epic Evolution (M) Sdn Bhd always looks for the customers wants to create and implement a successful strategy that will exceed customer satisfaction. The company operates in three branches that is Johor Bahru, Kuala Lumpur and Melaka. There are many types of event the company do such as property launch, concert and road show, conference, seminar, family day, product launches and others. Researcher do the research study on effectiveness of promotional tools used by Epic Evolution (M) Sdn Bhd come with the objectives of to determine the level of awareness of the public towards Epic Evolution (M) Sdn Bhd. Next is to determine the best promotional tools that can be used for Epic Evolution Sdn Bhd to promote their services to their customers and last is to know the relationship between effectiveness of promotional tools and 5 promotional tools. In this study, the researcher used the research design of descriptive research and causal research. For sampling technique, researcher used convenience sampling in non-probability for this study. Researcher distributed the questionnaire to respondents randomly around Johor Bahru to have primary data for data analysis and other sources are from journals. The researcher also gave recommendations for Epic Evolution (M) Sdn Bhd to improve their promotion efforts to become more effective.